A diagnostic framework to reveal future clean water scarcity in a changing climate - Shanlin Tong; Rui Xia; Jie Chen; Wenpan Li; Yan Chen; Chong-Yu Xu (Journal of Hydrology: Regional Studies)
Study region: The Yangtze River basin. Study focus: Clean water scarcity is one of the major constraints for human sustainable development. Previous diagnosis of water scarcity has focus on fluctuations in the amount of water needed by humans, while ignoring the imbalance between water supply and demand that is exacerbated by changes in water quality under the context of climate change. This study proposes a diagnosis framework for clean water scarcity analysis under future climate projections by combining climate and socioeconomic projections, hydrological system, environmental requirement and human water withdrawal simulations, and water quality projections. This framework is demonstrated in analyzing the clean water scarcity for near (2031–2060) and far (2070–2099) futures. New hydrological insights for the region: The results show that by the end of this century, the clean water stress index will decrease substantially, and the number of people potentially threatened by clean water scarcity is expected to decrease from 294.8 million to 159.1 million. Clean water scarcity is expected to ease as freshwater resources increase in the future. Based on scenario simulations, the results further reveal that mitigation measures for clean water scarcity are mainly affected by natural factors in near and far futures. These findings support that the proposed framework can provide a new perspective for assessing and explaining the multifaceted influences of climate change on clean water scarcity.